Distributed networks : intelligence, security, and applications - Memon, Qurban A. (CRC Press, 2014)
"Intelligent systems have numerous civilian, homeland security, and military applications; however, these applications carry certain requirements like communication bandwidth, sensing range, power constraints, stealth requirements prior to managing a centralized command and control. With contributions from leading scholars and experts, this book provides an in-depth exploration of emerging integration security. It includes theory and practical insights into distributed network intelligence, distributed network intelligence architectures, and applications and new trends in security. It explores the development of systems that are more scalable, flexible, and robust"--